(untitled) (Journal of Applied Oral Science, 2007)
OBJECTIVE: The purpose of this study was to evaluate the accuracy of relative measurements from the roof of the mandibular canal to the alveolar crest in multislice (multidetector) computed tomography (MDCT) and single-slice computed tomography (SSCT). MATERIAL AND METHODS: The sample consisted of 26 printed CT films (7 SSCT and 19 MDCT) from the files of the LABI-3D (3D Imaging Laboratory) of the School of Dentistry of the University of São Paulo (FOUSP), which had been acquired using different protocols. Two observers analyzed in a randomized and independent order a series of 22 oblique CT reconstructions of each patient. Each observer analyzed the CT scans twice. The length of the mandibular canal and the distance between the mandibular canal roof and the crest of the alveolar ridge were obtained. Dahlberg test was used for statistical analysis. RESULTS: The mean error found for the mandibular canal length measurements obtained from SSCT was 0.53 mm in the interobserver analysis, and 0.38 mm for both observers. On MDCT images, the mean error was 0.0 mm in the interobserver analysis, and 0.0 and 0.23 mm in the intraobserver analysis. Regarding the distance between the mandibular canal roof and the alveolar bone crest, the SSCT images showed a mean error of 1.16 mm in the interobserver analysis and 0.66 and 0.59 mm in the intraobserver analysis. In the MDCT images, the mean error was 0.72 mm in the interobserver analysis and 0.50 and 0.54 mm in the intraobserver analysis. CONCLUSION: Multislice CT was demonstrated a more accurate method and demonstrated high reproducibility in the analysis of important anatomical landmarks for planning of mandibular dental implants, namely the mandibular canal pathway and alveolar crest height.